OPTIMIZATION OF AGING PROCESS ON CLOSED-CELL ALUMINIUM FOAM USING BOX BEHNKEN DESIGN - NORIDAN, NOR AMEYZAH (IRC, 2018)
This study relate to improvement of physical and mechanical properties of closed-cell aluminium foam by optimization of aging process using Box Behnken Design. It is necessary to understand well on the effects of aging process parameters for obtaining optimal parameters and strengthening the properties of closed-cell aluminium foam. The literature review emphasizes the manufacturing process, parameters which influence aging process, design of experiments and post treatment which is quenching. The three aging process parameters are heating rate, temperature aging and time aging. These process parameters are studied and investigate by 17 experiments based on Box Behnken Design. Optical microscope is a light- magnifying lens to examine the microstructure of specimens. Besides, Scanning Electron Microscope (SEM) and Energy Dispersion X-ray Spectroscope (EDX) are carried out for surface topography and compositional analysis of closed-cell aluminium foams. To evaluate the hardness and strength of specimens, microhardness Vickers test and compression test are carried out. The highest Vickers Hardness Strength and Compression Strength is Sample 2 which is 395.12 HV and 4.9 MPa with time aging ( i e e e gi g d he i g e i ). No cracks detected after 3.5% Brine solution of Quenching process. Prediction and Validation of aging process parameters were conducted in order to verify the coded equation given by Analysis of Variance (ANOVA). Based on the setting parameters, too high or too low of aging process parameters will leads to low value of hardness and compression. It is also will produce large grain size and low total grain boundary area which increase the dislocation motion.